IRRIGAÇÃO E ADUBAÇÃO NITROGENADANO FEIJOEIRO COMUM CULTIVAR BRS ESTILO - FRANCO, jhonatan da silva; LOPES, Adriano da Silva; KRAESKI, Marcos Jefferson; MEDEIROS, Rosevaldo Domingos; SILVA, Gustavo Dantas Souza (ANAIS DO ENIC, 2023)
-